SIG WEB PUSAT-PUSAT LAYANAN PEMERIKSAAN COVID-19 DI KOTA PADANG - Ade Perdana Putra; Arie Yulfa (DEPARTEMEN GEOGRAFI FIS UNP, 2026)
This study aims to find out: 1) The process of designing and developing a data management system for the Covid-19 Health Health Service Facility in the City of Padang based on a web GIS. 2) The quality of the system developed is based on the web quality and web application assessment standards from WEBQEM. This research was conducted using a research and development approach. This type of research is classified as mixed research (Mix Method) because in the system development process the waterfall development methodology and qualitative approach are used in the system quality testing process. The results of this study resulted in: 1) A system that can manage data on health facilities for Covid-19 examinations in the City of Padang and users who can manage the system, application demos can be viewed at the address http://fasyankescovid-19padang.my.id/ 2) The system built has met the quality of a system based on the standardized quality assessment of websites and WEBQEM web applications. The conclusion is based on the results of the system testing which includes several tests: 1) the functionality test on this variable gets a final value of 1, which means the system has good functionality. 2) reliability testing on this variable using the LOADER.IO application where the results of the percentage of stress tests carried out on the system by charging 30 users traffic in 1 minute with a success rate of 98 and failure 0 and the average system response time of 1698ms, based on these results the system has met the standards in the aspect of reliability. 3) efficiency testing on this variable using GTMatrix software which produces an average value of 84.6 and the average grade obtained is B with an average response time to the server of 1.5ms. 4) this usability test gets a percentage of 91.3% which indicates the system has met the usability aspect standards.